Clinical features, aetiology and outcome of bacteraemic pneumonia in neutropenic cancer patients. Issue 8 (14th July 2016) - Gudiol, Carlota; Royo‐Cebrecos, Cristina; Laporte, Júlia; Ardanuy, Carmen; Garcia‐Vidal, Carolina; Antonio, Maite; Arnan, Montserrat; Carratalà, Jordi
ABSTRACT: Background and objective: We aimed to assess the clinical features, aetiology and outcomes of bacteraemic pneumonia in neutropenic cancer patients (NCP) in the current era of increasing antimicrobial resistance. Methods: All episodes of bacteraemia occurring in hospitalized patients with cancer, including haematopoietic stem cell transplant recipients, from January 2006 to April 2015 were included. Results: We identified 1723 episodes of bacteraemia, of which 795 occurred in neutropenic patients with cancer, and among them, 55 episodes were identified as bacteraemic pneumonia. The most frequent causative agents were Pseudomonas aeruginosa (39.6%), Streptococcus pneumoniae (20.6%) and Escherichia coli (8.6%). Among the Gram‐negative organisms, 12.8% were multidrug resistant (MDR). Eleven patients (20%) required admission to intensive care, and eight (14.8%) underwent invasive mechanical ventilation. Nine patients (16.3%) received inadequate empirical antibiotic therapy, of whom six (66.6%) died; eight of these nine patients had pneumonia caused by resistant microorganisms. The early (48 h) case‐fatality rate was 24% and the overall (30 day) case‐fatality rate was 46.2%. Conclusion: Bacteraemic pneumonia is a frequent complication among NCP and is mainly caused by P. aeruginosa and S. pneumoniae . The emergence of MDR organisms is of special concern. Despite the improvement in the management of cancer patients, case‐fatality rates of NCP with bacteraemic pneumonia remain high. Urgent assessment is needed to identify a better approach for the management and support of these patients. Abstract : Bacterial pneumonia is a frequent complication in cancer patients. However, recent information regarding this often life‐threatening complication is scarce. The aim of this study is to review the clinical features, aetiologies and outcomes of bacteraemic pneumonia in neutropenic cancer patients in the current era of widespread antibacterial resistance.